Therapeutic potential of exosomes in periodontal regeneration: Immunomodulatory and tissue-repair mechanisms - Yang, Shuang; Han, Chunyu; Wang, Qihui; Ai, Yicen; Wang, Dezhou; Song, Wenzhi (Frontiers in Immunology, 2025)
Periodontitis, a chronic inflammatory disease leading to irreversible tissue destruction, is a highly prevalent oral disease. The clinical management of periodontitis is challenging because conventional treatments like mechanical debridement and antibiotic therapy lack sufficient regenerative efficacy to achieve functional periodontal restoration. In recent years, exosomes have received widespread attention as cell-free therapeutic agents for periodontal tissue regeneration. This article reviews the dual role of exosomes in modulating immune response and promoting tissue repair, and briefly describes the exosome delivery systems studied so far. The aim of this review is to emphasize the important position occupied by cell-derived exosomes in the treatment of periodontitis as well as the main mechanisms, and to explore novel targets for the treatment of periodontitis.